2015
DOI: 10.1016/j.envres.2014.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the recovery of feeding rates in post-exposure feeding bioassays: Cyathura carinata as a case study

Abstract: Post-exposure bioassays are used in environmental assessment as a cost-effective tool, but the effects of organism's recovery after exposure to pollutant has not yet been addressed in detail. The recoveries of post-exposure feeding rates after being exposed to two sublethal concentrations of cadmium during two different exposure periods (48h and 96h) were evaluated under laboratory conditions using the estuarine isopod Cyathura carinata. Results showed that feeding depression was a stable endpoint up to 24h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…A delayed mortality was found in P. antipodarum after short-term exposure to cadmium (48-96h) (Jensen and Forbes 2001 ). Other studies have shown similar trends (Zhao and Newman 2006 ; Pais-Costa et al 2015 ). Therefore, the inclusion of post-exposure/recovery periods after toxicant exposure is an improvement in the realism of laboratory bioassays, as it allows a better prediction of the fate of field populations (Zhao and Newman 2006 ; Pais-Costa et al 2015 ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A delayed mortality was found in P. antipodarum after short-term exposure to cadmium (48-96h) (Jensen and Forbes 2001 ). Other studies have shown similar trends (Zhao and Newman 2006 ; Pais-Costa et al 2015 ). Therefore, the inclusion of post-exposure/recovery periods after toxicant exposure is an improvement in the realism of laboratory bioassays, as it allows a better prediction of the fate of field populations (Zhao and Newman 2006 ; Pais-Costa et al 2015 ).…”
Section: Discussionsupporting
confidence: 72%
“…Other studies have shown similar trends (Zhao and Newman 2006 ; Pais-Costa et al 2015 ). Therefore, the inclusion of post-exposure/recovery periods after toxicant exposure is an improvement in the realism of laboratory bioassays, as it allows a better prediction of the fate of field populations (Zhao and Newman 2006 ; Pais-Costa et al 2015 ). In fact, in our study, the mortality among non-stressed animals at the highest cadmium concentration at the end of the recovery was more than twice that found at the end of the exposure period.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation